Comparative study of anti-inflammatory property of calcium channel blocker and aspirin in albino rats - Jabeen, Anjum (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Calcium channel blockers are being used in the treatment of hypertension, ischemic heart disease, cardiac arrhythmias etc. They act by blocking the slow calcium channels. Influx of calcium is an essential step in the release of histamine and 5HT from mast cells and in the synthesis and release of prostaglandins. They are the main mediators in the process of inflammation. The aim of the present study was to compare anti-inflammatory properties of calcium channel blockers and aspirin in albino rats. Methods: Present study was prospective intervention study carried out to compare anti-inflammatory properties of calcium channel blockers and aspirin in albino rats. Total 30 albino rats were used, and they were divided into 5 groups of 6 each. First group of rats was control group where normal saline was used. Second group was standard group where aspirin was used. Remaining three groups were test groups and given nifedipine, amlodipine and diltiazem respectively. Effects were observed and compared between the groups. Results: In carrageenan method, the anti-inflammatory response of Aspirin was significantly higher. Nifedipine response was <aspirin but >diltiazem. The response of amlodipine was not significantly > that of control percent inhibition. In histamine method, the anti-inflammatory response of aspirin was significantly highest. Anti-inflammatory response of nifedipine was < aspirin but > diltiazem. Diltiazem response was < nifedipine but > amlodipine. In formaldehyde method, aspirin inhibition was highest at 96.2% followed by nifedipine (90.7%), diltiazem (75.9%) and amlodipine (3.7%). In cotton wool pellet granuloma, the mean dry granuloma weight was least for aspirin and percent anti-inflammatory activity was significantly high. Conclusions: Calcium channel blockers (nifedipine, diltiazem) have shown comparable anti-inflammatory property with that of aspirin. Further clinical studies are required for confirmation.